2019
DOI: 10.1111/joa.12974
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect on myelination through abolition of activity‐dependent synaptic vesicle release or reduction of overall electrical activity of selected cortical projections in the mouse

Abstract: Myelination of axons by oligodendrocytes in the central nervous system is crucial for fast, saltatory conduction of action potentials. As myelination is central for brain development and plasticity, and deficits are implicated in several neural disorders such as multiple sclerosis, major depressive disorder, bipolar disorder and schizophrenia, it is important to elucidate the underlying mechanisms regulating myelination. Numerous mechanisms have been proposed by which the communication between oligodendrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Our expression analyses established that Itpr2 is highly upregulated in differentiating OLs at early postnatal stages (Figure 1 and Supplementary Figure 1) when oligodendrocytes undergo active differentiation and myelination (Franco-Pons et al, 2006;Korrell et al, 2019). In fact, its expression is not detected in immature OPCs in embryonic tissues and is downregulated after axonal myelination in adult tissues (Figure 1 and Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our expression analyses established that Itpr2 is highly upregulated in differentiating OLs at early postnatal stages (Figure 1 and Supplementary Figure 1) when oligodendrocytes undergo active differentiation and myelination (Franco-Pons et al, 2006;Korrell et al, 2019). In fact, its expression is not detected in immature OPCs in embryonic tissues and is downregulated after axonal myelination in adult tissues (Figure 1 and Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 71%
“…To assess the in vivo role of Itpr2 in regulating OLs differentiation and myelin development, we next examined the expression of mature OL marker Plp1 in postnatal brain tissues by ISH. It was found that the number of Plp1 + myelinating OLs in Itpr2 –/– corpus callosum was significantly lower than that of controls between P7 and P15 stages ( Figures 2A–B′,D ) when OLs undergo active differentiation and myelination in this region ( Franco-Pons et al, 2006 ; Korrell et al, 2019 ). Intriguingly, the number of Plp1 + OLs was not altered in P21 control and mutant tissues ( Figures 2C,C′,D ).…”
Section: Resultsmentioning
confidence: 95%
“…Indeed, myelin sheath length can be remodeled once it is established; however, these changes are relatively rare in adulthood and sensory enrichment failed to induce any measurable changes in sheath length in rodents (Hill et al, 2018;Hughes et al, 2018). Alternatively, conduction velocity could be tuned by changes in nodal gap length, which can be modulated in adult mice (Dutta et al, 2018), upon neuronal activity changes (Cullen et al, 2019;Korrell et al, 2019).…”
Section: Myelination In Adulthood As An Adaptive Mechanismmentioning
confidence: 99%
“…In addition, recent observations in the central nervous system (CNS) indicate that myelin contributes to fine-tuning of neural circuits ( Fields, 2015 ; Chang et al, 2016 ; Kaller et al, 2017 ). For instance, myelin sheaths and nodes of Ranvier, ion channel–enriched axon segments interspersed between myelin sheaths, show activity-dependent plasticity ( Huff et al, 2011 ; Gibson et al, 2014 ; Mensch et al, 2015 ; Etxeberria et al, 2016 ; Korrell et al, 2019 ; Bacmeister et al, 2020 ) that appears to shape “patchy” myelination patterns in neocortex ( Tomassy et al, 2014 ). While activity-regulated myelination is less studied in the peripheral nervous system (PNS; Stevens and Fields, 2000 ; Fields, 2015 ), in the PNS, the axon–glial unit is more accessible than in the CNS, and the signaling pathways governing peripheral myelination are better understood ( Taveggia et al, 2010 ; Pereira et al, 2012 ; Grigoryan and Birchmeier, 2015 ).…”
Section: Introductionmentioning
confidence: 99%